Influence of Physical Health on Spirituality and Psychological Well- Being Among Elderly - Singh, Ritu; Mehra, Manisha (Indian Journal of Extension Education, 2020)
Unpredictable and unmanageable health issues challenge the threshold of tolerance and limitations ofÂ capabilities in old age. This may in turn upset the psychological equilibrium of the elderly. In such times, spirituality acts as a strong support base for providing psychological strength enabling them to transcendÂ their current feelings and circumstances. Contemplating this traditional notion, present study was taken up to assess the level of psychological well-being and spirituality among institutionalized and non-institutionalizedÂ elderly across their health status. The sample includes two categories of elderly individuals i.e., institutionalized (100) and non-institutionalized (100) selected from Uttarakhandâ€™s SRA-recognized old-age homes by censusÂ technique and by lottery technique from neighboring areas of old-age homes respectively. Standard Spiritual Belief Scale and Psychological Well Being Scale were employed to assess spirituality and psychologicalÂ wellbeing. Analysis across health status revealed that irrespective of the residential status, composite spirituality and psychological well-being was reported to be significantly higher in elderly with controllable health problems as compared to elderly with serious health problems.